Våld och Visioner. Möten med högre makter i Peter de Dusburgs Cronica Terre Prussie - Borg, Magnus (Collegium Medievale, 2019)
The Cronica Terre Prussie by Peter de Dusburg (c. 1330) chronicles the expansion of the Teutonic Order into Prussia and the Baltic region. Predominantly occupied with armed conflict, the work also contains a considerable number of accounts of miracles and wonders, the contents of which have not previously been studied as a corpus. This article attempts a quantitative and qualitative analysis of these accounts and argues that they serve as ideological propagandist vehicles for explaining and justifying the occupation of the Prussian and Baltic lands by the Teutonic Order. The article also suggests the possibly intended use of the chronicle to serve as a didactic basis and a knowledge framework for sermons, and as such that the intended primary audience would have been the priest brethren of the Teutonic Order.